Effect of ZnCO3 on the elastic and optical properties of glasses from soda-lime-silica glass and blast furnace slag - Mohd. Nazmi Mohd. Nazari (2008., 2008)
The purpose of this project is to investigate the effect of ZnCO3 on the elastic properties of glass from soda-lime-silica glass and blast furnace slag. In this work, different temperature of heat treatment 650°C, 690°C, 730°C, 770°C and 810°C were investigated. The ultrasonic wave velocities of these glasses have been investigated at room temperature by using pulse echo overlap technique. The elastic properties such as Young's modulus, bulk modulus, Poisson's ratio, and second order elastic stiffness constants were calculated from velocity measurements. The microstructure of samples was studied by the XRD spectrum. Refractive indices of the glass samples were determined by using Abbe refractometer. Ultrasonic method was used to carry out the studies of the elastic properties of glass samples. The values of both longitudinal and shear velocities which propagate in the glass were determined by using MBS-8000. Results from the studies showed that the densities of samples were linearly increased as the temperature of heat treatment increased. The longitudinal and shear wave velocities and the elastic constants such as C11, C44 and Young's modulus and Poisson's ratio of these glasses increased as temperature of heat treatment increased. The XRD spectrum indicated that homogenous glassy characters without showing any crystalline peaks or fully amorphous. The behavior of the elastic properties is related to the change in the structure of glasses with different temperature of heat treatment.
Project paper (B.S.(Hons.)) - Universiti Putra Malaysia, 2008.